Sustentabilidade ambiental na indústria petrolífera: uma análise das estratégias de transição energética da petrobras no período 2003-2023 - Serrão Neto, Walter (2025)
The energy transition is a central theme on the global agenda, driven by the need to reduce dependence on fossil fuels, which still account for approximately 82% of the world's energy production. Over the decades, the oil industry has established itself as one of the most influential and profitable sectors, playing a crucial role in the global economy. However, the environmental impacts and climate change associated with the burning of the fossil fuels, the main source of greenhouse gas (GHG) emissions, highlight the urgency of transforming the global energy matrix towards less polluting sources. This process challenges the oil and gas industry, which faces the dilemma of accelerating its energy transition without compromising existing investments in research, development, and innovation (RD&I) in traditional exploration and production areas. In the specific case of Petrobras, from 2003 to 2023, sustainability and energy transition strategies were strongly influenced by the characteristics of the incumbent governments. Governments with a more interventionist approach prioritized long-term investments, including in energy transition, while market-oriented governments focused on short-term financial results, downgrading environmental and energy transition issues to secondary importance. This study analyzes Petrobras’ evolution in this political context, considering the impact of environmental agreements to combat global warming and corporate guidelines on the sustainability of its operations. The methodology combined document analysis of Petrobras’ financial and sustainability reports, studies from industry agencies, climate non-governmental organizations, and comparisons with international majors operating in Brazil. The results show that, although Petrobras has advanced in operational efficiency and decarbonization, particularly with technologies such as carbon capture, utilization, and storage (CCUS), applied mainly due to pre-salt operational needs, the company has moved away from strategic areas in renewable energies such as biofuels, onshore and offshore wind energy, solar energy, and hydrogen. These technologies are the focus of leading global oil companies due to their synergy with existing infrastructures and the sector's accumulated expertise. A comparison with companies such as Shell, BP, Total, and Equinor, which are major players operating in Brazil, reveals that Petrobras lags in the race to diversify the energy matrix, although it surpasses operators like PetroChina in terms of adherence to market best practices. Thus, to maintain its relevance in the medium and long term in an increasingly regulated and competitive market, Petrobras must integrate clean technologies, adopt stricter sustainability standards, and balance economic growth with technological innovation. The pricing of GHG emissions and the pressure for policies aligned with ESG agendas make this balance essential for the company’s future